Laser at 532 nm by intracavity frequency-doubling in BBO - Yuan, Xiandan; Wang, Jinsong; Chen, Yongqi; Wu, Yulong; Qi, Yunfei; Sun, Meijiao; Wang, Qi (Journal of semiconductors, 2017)
A simple and compact linear resonator green laser at 532 nm is generated by intracavity frequencydoubling of a diode-side-pumped acousto-optically（AO）Q-switched Nd：YAG laser at 1064 nm.Two acoustooptic Q-switches were placed orthogonally with each other to improve the hold-off capacity.As high as 214 W of continuous-wave（CW）and 154 W of quasi-continuous-wave（QCW）output power at 1064 nm were obtained when the pumping power was 1598 W.The type I phase-matched BBO crystal was used as the nonlinear medium in the second harmonic generation.A green laser with an average output power of 37 W was obtained at a repetition rate of 20 kHz and a pulse width of 54 ns,which corresponds to pulse energy of 1.85 mJ per pulse and a peak power34.26 kW,respectively.